Analisis Wacana Kritis Norman Fairclough Representasi Kehidupan Religius Cerpen Mbah Sidiq Karya A. Mustofa Bisri - Ervania; Teguh Setiawan; Nurhayadi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Critical discourse analysis (AWK) is one of the views on language in discourse analysis which views powers as always involved in the formation of subjects represented in language. The AWK model used in this paper is Norman Fairclough's critical discourse analysis. Critical discourse analysis which generally analyzes media texts can also be done to analyze literary works including short stories. The short story analyzed by Norman Fairclough's discourse analysis is Mbah Sidiq's short story by A. Mustofa Bisri which is presented in the book Collection of Short Calligraphy Paintings. In Norman Fairclough's discourse analysis, texts, discourse practice, and sociocultural practice are examined. Through the descriptive method, finally the three aspects of Norman Fairclough's discourse analysis can be answered. In the text section, the researcher can find three basic elements in the Norman Fairclough model, namely the elements of representation, relations and identity in Mbah Sidiq's short story. While this paper will only discuss one element, namely representation. Mbah Sidiq's short story above is an Islamic short story with a Javanese cultural background. The short story displays a portrait of the life of the Javanese and Indonesian Islamic communities. In addition, Gus Mus, through his short stories, also tries to criticize the behavior and social conditions of Javanese society and Indonesian Islamic society in general, which still cannot separate religious spiritual behavior from ancestral traditions which sometimes contradict Islamic teachings. This was done because Gus Mus in his daily life is a kiai, a preacher who cares for a boarding school, which incidentally is someone who has deeply studied and mastered the Islamic sciences.